Does Exposure of Smart Phones during Pregnancy Affect the Offspring's Ovarian Reserve? A Rat Model Study. (15th April 2021) - Calis, Pinar; Seymen, Merve; Soykan, Yagmur; Delen, Kevser; Aral, Bahriye Sirav; Take Kaplanoglu, Gulnur; Karcaaltincaba, Deniz
Abstract: Objective: We investigated the effect of prenatal exposure to smart phone radiation and the protective effect of omega-3 on ovarian reserve of offspring. Methods: 24 pregnant Wistar albino rats were divided into four groups. Group-I received neither radiofrequency (RF) radiation nor omega-3, group-II received RF, group-III received RF radiation and 300 mg omega-3 and group-IV received RF radiation and 600 mg Omega-3 till birth. At 42 days, bilateral oophorectomy was performed on all female offspring for follicle count and immunohistochemical staining (GDF9, FOXO1 and TUNEL). Results: Group-II had significantly lower mean number of primordial (p = 0.006), secondary follicles(p = 0.003) and a higher atresia score. Group-III variables were comparable with group-I variables. Group-IV had statistically higher median number of atretic follicles than group-I (p = 0.023). Conclusions: Ovarian reserve of offspring diminished with RF exposure during pregnancy. Omega-3 supplementation during pregnancy may reduce the potential premature ovarian failure.